2011
DOI: 10.1007/s11105-011-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-Mediated In Planta Transformation of Field Bean (Lablab purpureus L.) and Recovery of Stable Transgenic Plants Expressing the cry1AcF Gene

Abstract: The amenability and reproducibility of a tissue culture-independent Agrobacterium tumefaciens-mediated transformation strategy was analyzed in field bean and the stability of the transgenes was examined. The protocol involves in planta inoculation of embryo axes of germinating seeds and allowing them to grow into seedlings ex vitro. Transformants were raised using a chimeric Bt gene, cry1AcF, and putative transformants were analyzed by PCR for both cry1AcF as well as the nptII genes. Bioassays against Helicove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…It was concluded that this novel system promoted the gene expression in switchgrass by significantly enhancing the GUS expression percentage from 6 to 54 % with the application of 100 lM acetosyringone (Chen et al 2010). Keshamma et al (2012) conducted a study on in planta transformation in field bean by inoculating embryo exes from 2-day-old seedlings as explants and ascertained that incubation period of 1 h proved to be effective for efficient transformation in field bean with stability of foreign genes through three successive generations. Another successful tissue culture-independent in planta approach was developed for revitalizing the genetic improvement in Capsicum annuum using 4-day-old seedlings and found that forty minute incubation period for intercotyledonary region injured with a needle yielded the highest TE in bell pepper (Kumar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that this novel system promoted the gene expression in switchgrass by significantly enhancing the GUS expression percentage from 6 to 54 % with the application of 100 lM acetosyringone (Chen et al 2010). Keshamma et al (2012) conducted a study on in planta transformation in field bean by inoculating embryo exes from 2-day-old seedlings as explants and ascertained that incubation period of 1 h proved to be effective for efficient transformation in field bean with stability of foreign genes through three successive generations. Another successful tissue culture-independent in planta approach was developed for revitalizing the genetic improvement in Capsicum annuum using 4-day-old seedlings and found that forty minute incubation period for intercotyledonary region injured with a needle yielded the highest TE in bell pepper (Kumar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, infection of germinating seeds have been found as better explants source for efficient in planta transformation strategy in various crops such as Medicago truncatula, radish and brinjal (Trieu et al 2000;Park et al 2005;Subramanyam et al 2013). This novel strategy for gene transfer is crucial for crop species whose transformability is challenging one due to recalcitrance of in vitro regeneration (Keshamma et al 2012) but during in planta transformation chimeras is a serious problem which can be circumvented by strong selection system (Mayavan et al 2013;Subramanyam et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Broad‐spectrum insecticidal activity of cry1AcF following binding to APN1 receptors of H. armigera and Spodoptera litura was reported through both in silico as well as transgenic approaches. The ability of the chimeric gene to demonstrate multi‐pest efficacy was earlier demonstrated in crops like pigeon pea, groundnut, castor and field bean …”
Section: Introductionmentioning
confidence: 97%
“…The ability of the chimeric gene to demonstrate multi-pest efficacy was earlier demonstrated in crops like pigeon pea, 17 groundnut, 30 castor 31 and field bean. 32 Furthermore, cry2Aa (GenBank accession id: ABW87832.1), another synthetic gene, has a modified codon usage for plants and is also known to exhibit broad-spectrum specificity as its native protein towards two insect orders, Lepidoptera and Diptera. It is highly lethal towards lepidopteran pests in comparison to cry1 proteins, as evidenced by its structure and toxicity studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported successful transformation of B. napus with Agrobacterium tumefaciens (Chhikara et al, 2012). These transformation technologies can be used for gradual crop improvement, as they have been used to produce novel improved traits, such as herbicide tolerance (Konagaya et al, 2013), regulated oil composition (Knutzon et al, 1992), insect resistance (Keshamma et al, 2012), and salt tolerance (Dhaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%